THE RESEARCH WORK OF THE LANDSCAPE GROUP OF ISCEAH – IDENTIFYING AND DISCUSSING CASE STUDIES - Kanan, Isabel; Cooke, Louise; Bell, Jonathan (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
This paper intends to present the ongoing research efforts that the earthen-architectural cultural-landscape group, one of the ive scientiic research groups within ISCEAH (International Scientiic Committee on Earthen Architectural Heritage), is undertaking. After the last Terra Conference, in Mali, 2008, the group committed to identifying and deining the boundaries, various building technologies, conigurations and typologies of earthen cultural landscapes. The methodology includes the selection of case studies by members and the creation of a graphic spreadsheet containing data based on research and ieldwork. Important aspects, such as archaeological, historical and contemporary uses of earth, present-day threats, changes in use, socio-cultural issues and efforts towards sustainable development are under discussion. The paper presents the themes discussed by the group, theoretical considerations and practical concerns identiied by the case studies, and key issues of earthen-architecture cultural landscapes that provide a foundation for future work.